Kontribusi PKB Dan BBNKB Bagi Pajak Daerah Provinsi Jawa Barat - Michellevanessa Pandingan; Joan Yuliana Hutapea (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Local Taxes are one of the local government revenues that is beneficial for financing and developing a region. Each region has revenues that sometimes result in inequality in the development of an area, due to differences in the potential of each region. Local tax revenue is one of the largest contributors to Local Own-Source Revenue (PAD). This study aims to retest the contribution of Motor Vehicle Tax (PKB) and Tax of Transfer Vehicle Ownership (BBNKB) to local taxes revenue in West Java Province in 2015-2022. This study used quantitative methods with a causal associative analysis process. Statistical data processing uses descriptive analysis, correlation and determination efficiency, regression and significance tests from data on the realization of PKB, BBNKB and local taxes revenues. The results of observations based on statistical analysis show that local taxes are influenced by PKB (sig. 0.00 < 0.05) but not by BBNKB (sig. 0.06 > 0.05). Simultaneously, local taxes are affected by PKB and BBNKB (sig. 0.00 < 0.05).